The Outbreak of Covid-19 as an Overmacht Claim in Credit Agreements - Merry Tjoanda; Yosia Hetharie; Marselo V.G Pariela; Ronald F. Sopamena (Fiat Justisia: Jurnal Ilmu Hukum, 2021)
This research aims to determine and analyze the law consequences of overmacht in credit agreements due to the Covid-19 Pandemic and as legal remedies for settlement of the credit agreement due to the Covid-19 Pandemic. This research is socio-legal research, a combination research method between doctrinal law research methods and empirical legal research methods. This research was conducted in banking institutions and financing institutions in Ambon City, namely at Bank Mandiri Ambon Branch Office, BCA Ambon Branch Office, Bank Artha Graha Ambon Branch Office, and BFI Limited Company Ambon Branch Office. The types of research data are primary data and secondary data, obtained through literature study and interviews. Based on the results of the research, the Covid-19 Pandemic is a non-natural disaster, so it is categorized as a relative overmacht, so the result of the comparative overmacht law in the credit agreement due to the Covid-19 Pandemic in Ambon City has not changed the risk burden in the sense that the Debtor still fulfills their achievements after the outbreak of Covid - 19 Pandemic is over. The legal effort that can be taken to settle credit agreements due to Covid-19 Pandemic in Ambon City is through credit restructuring in the form of lowering interest rates, extending the period, reducing principal arrears, and reducing interest arrears as determined by the government to be implemented by the bank or financing institutions with debtors.